Pengembangan Kemampuan Sumber Daya Manusia melalui Pelatihan Komputer Microsoft Office Excel untuk Meningkatkan Kinerja Perangkat Desa Pungkang Lauk, Kecamatan Aikmel, Lombok Timur - Widia Febriana; Lela Rahmawati; Melati Rosanensi; Zahrah Zahrah; Lanang Sakti (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
In facing the era of globalization which is growing rapidly at this time, especially with the development of increasingly advanced science and technology, it is essential to have adequate skills to support the performance of village officials in Pungkang Lauk Village, Aikmel District, East Lombok. This is because in service activities to the community, the village apparatus of Pungkang Lauk, Aikmel District, and East Lombok still have not utilized their potential optimally in operating Microsoft Office programs. This condition certainly has an impact on the less than optimal performance of village officials in serving the community. The purpose of this Community Service is to provide training and improve and maximize the potential of human resources on how to operate computers in the Microsoft Office Excel program on the Pungkang Lauk Village device, Aikmel District, East Lombok, so that they can better serve the needs of the village community. Implementing Community Service activities is a method of training, practice, and question and answer. While the target audience is villagers, especially village officials in Pungkang Lauk Village, Aikmel District, and East Lombok who want to maximize the existing potential by operating computers better. By holding Community Service Activities through training in operating computers, especially village officials in Pungkang Lauk Village, Aikmel District, and East Lombok, can add insight and knowledge and improve the performance of village officials more optimally in providing services to the community as desired by the government.